2019
DOI: 10.3389/feduc.2019.00114
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Adolescents’ Encounter With a Flipped Learning Intervention in Norwegian Physical Education

Abstract: Objective: The discrepancy between observed and suggested levels of physical activity among adolescents urges society to obtain more knowledge and insight into how physical education (PE) in school can be beneficial for all individuals. The purpose of the present study was to examine the perceptions of adolescents of a flipped learning (FL) framework, applied to enhance student motivation and learning in PE. Methods: Ten students, from 13 to 17 years of age, were recruited from one secondary school and one upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 63 publications
2
26
0
1
Order By: Relevance
“…An ad hoc questionnaire was used to collect the data, taking some validated instruments on the state of the matter [64,77,78]. The questionnaire consisted of 42 items.…”
Section: Instrumentmentioning
confidence: 99%
“…An ad hoc questionnaire was used to collect the data, taking some validated instruments on the state of the matter [64,77,78]. The questionnaire consisted of 42 items.…”
Section: Instrumentmentioning
confidence: 99%
“…The concept of FL in PE includes obtaining more time for practical activity and arranging for more physical and cognitive learning by the students in preparing prior to class. This preparation is preferably a video specific to the upcoming class and includes both practical information about the activities and theoretical knowledge underpinning the class topic/aim [67]. Very little research has been undertaken into the FL approaches [68] included in PE [69].…”
Section: Flipped Learningmentioning
confidence: 99%
“…Casey et al [70] argue that there is a lack of research on how digital technologies are used and how they affect motivation and learning in PE. However, there are studies suggesting that FL has a positive impact on student motivation in secondary school PE [71], especially among girls [72,73], and that both cognitive learning and perceived value of the subject are positively affected when a FL framework is applied in PE [67]. In a Chinese study of teaching basketball in PE, Chiang et al [74] concluded that female students benefit more from flipped learning strategies compared to boys.…”
Section: Flipped Learningmentioning
confidence: 99%
“…In short, different recent high-impact researches show the potentialities of the instructional approaches previously presented (Luong, 2019;Østerlie and Kjelaas, 2019;Quintas et al, 2020;Sargent and Casey, 2020). The novelty that this study presents concerning the existing literature focuses on the simultaneous integration of both training methodologies for the approach of contents linked to the subject of Physical Education.…”
Section: Introductionmentioning
confidence: 87%